1988
DOI: 10.1111/j.1399-3054.1988.tb09166.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on host and endophyte development in mycorrhizal soybeans in relation to water use and phosphate uptake

Abstract: 1988. Effects of drought on host and endophyte development in mycorrhizal soybeans in relation to water use and phosphate uptake. -Physiol. Plant. 72: 565-571. Soybean [Glycine max (L.) Merr.] plants were grown in pot cultures and inoculated with the vesicular-arbuscular mycorrhizal (VAM) fungus GIomus mosseae (Nicol. & Gerd.) Gerd. and Trappe or provided with P fertilizer (non-VAM plants). After an initial growth period (21 days), plants were exposed to cycles of severe, moderate or no drought stress over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 21 publications
3
37
1
1
Order By: Relevance
“…These mycorrhizal fungi also did not affect the total amount of soil water extracted before safflower and wheat plants wilted completely, even though soil hydraulic conductivity was probably very low under these dry soil conditions (c. 10"' cm d"' or less at 'F^ < -0-5 MPa (predicted as in van Genuchten, 1980). By contrast, Bethlenfalvay et al (1988) found fhat M soybean plants depleted soil water to a greater extent than NM soybean, and Hardie & Leyton (1981) found similar results in clover. In both studies, however, M plants were more intensely rooted and might have simply explored a greater soil volume than NM plants, whereas in the present study, mycorrhizal infection did not affect L^.…”
Section: Discussionmentioning
confidence: 99%
“…These mycorrhizal fungi also did not affect the total amount of soil water extracted before safflower and wheat plants wilted completely, even though soil hydraulic conductivity was probably very low under these dry soil conditions (c. 10"' cm d"' or less at 'F^ < -0-5 MPa (predicted as in van Genuchten, 1980). By contrast, Bethlenfalvay et al (1988) found fhat M soybean plants depleted soil water to a greater extent than NM soybean, and Hardie & Leyton (1981) found similar results in clover. In both studies, however, M plants were more intensely rooted and might have simply explored a greater soil volume than NM plants, whereas in the present study, mycorrhizal infection did not affect L^.…”
Section: Discussionmentioning
confidence: 99%
“…Such growth response to mycorrhizal colonization was previously observed in other olive variety (Rougemont, 2007) and many other plant species such as Citrus tangerine , Poncirus trifoliate (Wu et al, 2008), date palm Faghire et al, 2010), pistachio (Abbaspour et al, 2012) and carob . The positive effect on plant growth has been attributed to the improvement of water and nutrients uptake due to the greater absorption of the surface area provided by extensive fungal hyphae and the increased root length and density (Bethlenfalvay et al, 1988;Faber et al, 1991;Fouad et al, 2012Fouad et al, , 2013Essahibi et al, 2013). In previous study we showed enhanced water uptake and nutrients (potassium and phosphorus) accumulation in mycorrhizal olive plants compared to NMplants both under well watered and water def icit conditions (Fouad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Correlative evidence has linked soil aggregation with increased drought resistance (Davies et al 1992). Physiologically, mycorrhizae-mediated uptake of bound soil water may be analogous to the uptake of phosphorus, where tapping supplies not available to the nonAM plant results in a positive growth response (Bethlenfalvay and Schüepp 1994).…”
Section: Mycorrhizae and Soil Water Relationsmentioning
confidence: 99%
“…The findings support the assertion that external, soil hyphae may play an important role in mycorrhizal influence on the water relations of host plants. Bethlenfalvay and colleagues had suggested earlier that, theoretically, colonization of soil by hyphae might be expected to have as great (or greater) influence on host behavior during drought as colonization of roots (e.g., Bethlenfalvay and Linderman 1992). Others recently reported that, among six AM species tested, effectiveness in enhancing plant water uptake from soil appeared related to the amount of external mycelium produced by each AM fungus as well as to the frequency of root colonization in terms of live and active fungal structures (Marulanda et al 2003).…”
Section: Testing Contributions Of Soil Andmentioning
confidence: 99%